63.6k views
0 votes
T+25=26 solve for t

User Pushmatrix
by
5.6k points

2 Answers

1 vote

Answer: t = 1

Step-by-step explanation: To solve the equation t + 25 = 26, since 25 is being added to t, we need to subtract 25 from both sides of the equation.

On the left side of the equation, the +25 and -25 cancel each other out and we are simply left with t. On the right side, 25 - 26 is 1 so we have t = 1 which is the solution to our equation.

User Adam Gonzales
by
5.8k points
3 votes

Welcome!

Try writing the equation like this.

T = 26-25

Now, you need to simplify.

T= 1

You should get your final answer T = 1

You want to get T by itself, so you subtract 25 by itself to make it go away, but whatever you do to any side, you have to do it on the other side.

I apologize for the edits & mistakes I made. I've fixed them.

Sorry for any disturbance.

User Aleix CC
by
5.7k points